Optimum Scheme for Insulation System in HV Generator Based on Electromagnetic Analysis - Azizi, D.; Gholami, A. (Engineering, Technology & Applied Science Research, 2011)
Electrical insulations are one of the basic parts of electrical machinery in any sizes and characteristics. Focusing on insulating, studies on the operation of industrial-electrical machinery came to the fact that the most important part of a machine is the Stator. This fact reveals the requirement for inspection of the electrical machine insulation along with the electromagnetic tensions. Therefore with respect to insulation system improvement of stator, the HV generator can be optimized. Dielectric parameters such as insulation thickness, spacing, material types, geometry of winding and slot are major design consideration. A very powerful method available to analyze electromagnetic performance is Finite Element Method (FEM) which is used in this paper. The analysis of various stator coil and slot configurations are used to design the better dielectric system to reduce electrical stresses in order to increase the power of generator in the same volume of core. These processes of optimization have been done according the proposed algorithm. In this algorithm the technical constraints have been considered. This paper describes the process used to perform classical design and improvement analysis of stator slot’s insulation with respect to objective function and constraints.